Entre dos imperios: un elemento de control común y divergente. Las estadísticas demográficas en Cuba, Puerto Rico y Filipinas - Alejandro Román Antequera (Les Cahiers ALHIM)
Along the 19th century, the Spanish State improved its statistics system, even though it is true that it had had yet a significant development in the previous century, with a great exponent in the Floriblanca’s census (1787). This ability to elaborate statistics of the population was reproduced in the New World, where censuses were having a great quality. The encouraging panorama for Spanish demographic statistics was recovered after the hard beginning of the 19th century. This developed its ability for collecting data of the populations in the different territories under its control, at the same time as the elaboration of demographic statistics in the Iberian Peninsula. Nevertheless, this process was different between the metropolis and its colonies and within these. Therefore, the principal aim of this article is to analyze the how and the why of these divergences. Likewise, the elaboration of statistics of the Spanish State at its overseas territories along the 19th century will be compared with the labor of the United States’ new imperial power, at the end of the 19th and the beginnings of the 20th century.